Wildfire : a novel - Lowry, Mary Pauline (Skyhorse Publishing, 2016)
"Julie has an obsession with fire that began after her parents died when she was twelve years old. Her pyromania leads her to take an unlikely job as a forest firefighter on an elite, Type 1 "Hotshot" crew of forest firefighters who travel the American West battling wildfires. The only woman on the twenty-person crew, Julie struggles both to prove her worth and to find a place of belonging in the dangerous, insular, and very masculine world of fire"--